Knowledge and practice of intensive care physical therapists on the use of functional electrical stimulation (Research, Society and Development, 2022)
Objective: To ensure the knowledge and practice of intensive physical therapy professionals on the use of functional electrostimulation (FES), in order to observe the level of safety and practice of professionals. Methods: The present study has a cross-sectional approach of the CAP survey type (knowledge, attitude and practice), with a quantitative and descriptive analysis, with searches carried out in PubMed, SciELO, Medline and Cochrane databases. Being approved by the Ethics Committee of the Real Hospital Português, and sent to ASSOBRAFIR a virtual forms through Google Forms containing general information about the research, in addition to a questionnaire with 11 multiple choice questions involving simple and easy to understand questions, about the use of functional electrical stimulation in the ICU. Results: The sample size consisted of 20 professionals of both sexes, aged between 26 and 61 years, with a working time between 1 and 37 years, who answered whether they had the knowledge and whether or not they used the FES in their care. In intensive care unit patients. Conclusion: The survey results suggest that professionals have knowledge about the use of functional electrostimulation within the ICU, with 60% of them not using the technique frequently, and 50% using evidence-based protocols.